Why Are Vickrey Auctions Rare? - Rothkopf, Michael H.; Teisberg, Thomas J.; Kahn, Edward P. (Journal of Political Economy, 1990)
In 1961, William Vickrey showed that, in an independent private-values context with symmetric risk-neutral bidders, sealed second-price auctions have dominant truth-revealing equilibrium strategies; are perfectly efficient economically; and produce the same expected revenue for bid takers as equilibrium strategies in oral progressive auctions, Dutch auctions, or standard, first-price sealed bidding. Yet sealed second-price auctions seldom occur. The authors argue that fear of cheating and especially disincentives for bidders to follow truth-revealing strategies are important explanations. They model auctions in which third parties capture a fraction of the economic rent revealed by the second-price procedure. Copyright 1990 by University of Chicago Press.